2010
DOI: 10.1371/journal.pone.0009016
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Inflammatory Cytokines, IFNγ and TNFα, Influence Immune Properties of Human Bone Marrow and Wharton Jelly Mesenchymal Stem Cells Differentially

Abstract: BackgroundWharton's jelly derived stem cells (WJMSCs) are gaining attention as a possible clinical alternative to bone marrow derived mesenchymal stem cells (BMMSCs) owing to better accessibility, higher expansion potential and low immunogenicity. Usage of allogenic mesenchymal stem cells (MSC) could be permissible in vivo only if they retain their immune properties in an inflammatory setting. Thus the focus of this study is to understand and compare the immune properties of BMMSCs and WJMSCs primed with key p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
401
3
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 417 publications
(444 citation statements)
references
References 60 publications
34
401
3
6
Order By: Relevance
“…Based on our data, we cannot confirm that the observed IFNg + IL-10 + double-positive subpopulation is generated from a switched Th1 population, since we cannot trace single T-cell clones, and alternatively, the same cellular distribution could be due to Th1 cell death or either a cell survival advantage or selective expansion of IL-10-producing cells. Our observation that the major induction by MSCs of this particular T-cell phenotype occurred in the presence of allogeneic antigen-presenting cells is evidence for the commonly accepted notion that a proinflammatory environment favors the suppressive function of MSCs (the so-called licensing process) both in vivo and in vitro [31][32][33].…”
Section: Discussionsupporting
confidence: 66%
“…Based on our data, we cannot confirm that the observed IFNg + IL-10 + double-positive subpopulation is generated from a switched Th1 population, since we cannot trace single T-cell clones, and alternatively, the same cellular distribution could be due to Th1 cell death or either a cell survival advantage or selective expansion of IL-10-producing cells. Our observation that the major induction by MSCs of this particular T-cell phenotype occurred in the presence of allogeneic antigen-presenting cells is evidence for the commonly accepted notion that a proinflammatory environment favors the suppressive function of MSCs (the so-called licensing process) both in vivo and in vitro [31][32][33].…”
Section: Discussionsupporting
confidence: 66%
“…These inherent differences appear to be further enhanced by inflammation. These transcriptome studies are compatible with in vitro tissue source comparison studies [22][23][24] that find baseline and activated MSCs from BM, cord tissue, and ASC modulate the immune response and respond to inflammatory mediators distinctly [5,25]. Although research with MSCs from different tissue sources in horses is just beginning, equine MSCs appear to be remarkably similar to other species described to date.…”
Section: Msc Tissue Of Originsupporting
confidence: 64%
“…Our data might suggest that BM-MSCs have a weaker response overall and in particular for the radioprotection of vascular EC. Affirmative, earlier reports already suggested that BM-MSCs were less effective for MSC therapy compared to other stem cell sources, for example, compared to adipose tissue-derived or fetal MSCs (64,66,86).…”
Section: Murine Wt Bm (Xrt/bm) Cells From C57bl/6 Donor Mice Into Thementioning
confidence: 73%